Supraspinatus Intramuscular Calcified Hematoma or Necrosis Associated with Tendon Tear - Alexandre Lädermann; Muriel Genevay; Sophie Abrassart; Adrien Jean-Pierre Schwitzguébel (Case Reports in Orthopedics)
Introduction. Rotator cuff intramuscular calcification is a rare condition usually caused by heterotopic ossification and myositis ossificans. Case Presentation. We describe a patient with voluminous calcified mass entrapped in supraspinatus muscle associated with corresponding tendon tear. Histological examination corresponded to a calcified hematoma or necrosis. Patient was surgically managed with open excision of the calcified hematoma and rotator cuff arthroscopic repair. At 6 months, supraspinatus muscle was healed, and functional outcome was good. Discussion and Conclusion. We hypothesized that supraspinatus intramuscular calcified hematoma was responsible for mechanical stress on the tendon. This association has never been described.